Effect of Leaching of Ionic Rare Earth Ores on the Permeability Coefficient of Mineral Soil and Its Correlation with the State Parameter - Run Xiang; Yunzhang Rao; Jiyong Zhang; Laiye Zhang; Zhihua Yang (Metals)
The permeability of ionic rare is a crucial factor influencing the leaching rate of rare earth elements. In the Gannan region, many ionic rare earth ores exhibit poor permeability and high compressibility compared to sandy soils. The permeability coefficient is a key indicator of the hydraulic performance of these ores. Thus, this study investigates the permeability coefficients of ionic rare earth ores with varying fines contents during the leaching process, with a specific focus on analyzing the impact of fines on permeability performance. To provide a comprehensive assessment of the influence of fines, we prepared ionic rare earth ore samples with fines contents of 5%, 10%, 15%, 20%, 25%, and 30%, ensuring that the overall particle size distributions remained consistent with the original gradation. A constant head permeability test was employed to measure the permeability coefficients of these ore samples throughout the leaching process. We specifically examined how varying fines contents influenced permeability across the upper, middle, and lower layers of the ore body, as well as the overall permeability when subjected to both distilled water and magnesium sulfate solutions. To further elucidate the differences in permeability performance among the various rare earth ore samples, we performed a data fitting analysis of the initial permeability coefficients against fines content, uniformity coefficient, average particle diameter, and void ratio. This analysis aims to quantify the fines effect across different rare earth ores and establish correlations among state parameters, such as fines content, and the initial permeability coefficient.